68.3k views
6 votes
5x + (-x) - 1 = 11 - 2x

2 Answers

12 votes

Answer:

x = 2

Explanation:

5x + (- x) - 1 = 11 - 2x , that is

5x - x - 1 = 11 - 2x

4x - 1 = 11 - 2x ( add 2x to both sides )

6x - 1 = 11 ( add 1 to both sides )

6x = 12 ( divide both sides by 6 )

x = 2

User Mario David
by
6.5k points
5 votes

Answer:

The value of x is 2

Explanation:

=> 5x + (-x) - 1 = 11 - 2x

=> 5x -x -1 = 11 - 2x

=> 4x - 1 = 11 - 2x

=> 4x+2x = 11+1

=> 6x = 12

=> x = 12/6

=> x = 2

User Margus Pala
by
5.2k points